PENGOLAHAN LIMBAH PERTANIAN DAN KERAJINAN MENJADI PUPUK ORGANIK BERKUALITAS DI DESA TARO, KECAMATAN TEGALLALANG KABUPATEN GIANYAR - A.A.N.G. Suwastika; N. W. S. Sutari; A.A.A.A. S. Sunari; N.N. Soniari; I W. D. Atmaja Atmaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
This community service was held on Thursday, July 26, 2012 at Gapoktan Sarwa Ada”, the village of Taro,Tegallalang District, Gianyar regency. The method used in this activity through education and training with theaim at improving farmers’ knowledge in the processing agricultural waste and waste wood craft a quality organicfertilizer to use local microorganisms. Training wass going well and in the family atmosphere. Material extensionand how to manufacture quality organic fertilizer were easily understood by farmers. All farmers can make theirown organic fertilizer from organic waste. Preparation of local microorganisms as decomposers bioactivator was easyto handle. Knowledge of farmers on organic waste still needs to be improved to prevent environmental pollution.